1997
DOI: 10.1083/jcb.136.2.473
|View full text |Cite
|
Sign up to set email alerts
|

A Three-dimensional Collagen Lattice Induces Protein Kinase C-ζ Activity: Role in α2 Integrin and Collagenase mRNA Expression

Abstract: A three-dimensional collagen lattice can provide skin fibroblasts with a cell culture environment that simulates normal dermis. Such a collagen matrix environment regulates interstitial collagenase (type I metalloproteinase [MMP-1], collagenase-1) and collagen receptor α2 subunit mRNA expression in both unstimulated or platelet-derived growth factor–stimulated dermal fibroblasts (Xu, J., and R.A.F. Clark. 1996. J. Cell Biol. 132:239–249). Here we report that the collagen gel can signal protein kinase C (PKC)-ζ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 70 publications
7
75
0
Order By: Relevance
“…However, it cannot be excluded that TPA-independent PKC isoforms, not inhibited by BIM at this concentration, are involved in the up-regulation of the MMPs in RCG. Xu and Clark (1997) have indeed shown that PKC-ζ is activated in RCG and participates in the up-regulation of the MMP-1. Other authors (Sudbeck et al, 1994;Vincenti et al, 1996) and ourselves (Lambert et al, 1998) have also demonstrated that TPA-induced expression of MMP-1 is inhibited by tyrosine kinase inhibitors, suggesting that PKC may act upstream of Src in the upregulation of the MMPs by phorbol esters and CD, and possibly also in RCG.…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be excluded that TPA-independent PKC isoforms, not inhibited by BIM at this concentration, are involved in the up-regulation of the MMPs in RCG. Xu and Clark (1997) have indeed shown that PKC-ζ is activated in RCG and participates in the up-regulation of the MMP-1. Other authors (Sudbeck et al, 1994;Vincenti et al, 1996) and ourselves (Lambert et al, 1998) have also demonstrated that TPA-induced expression of MMP-1 is inhibited by tyrosine kinase inhibitors, suggesting that PKC may act upstream of Src in the upregulation of the MMPs by phorbol esters and CD, and possibly also in RCG.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars show SE values. (Ivaska et al, 1999;Ravanti et al, 1999), the isoform of PKC (PKC ; Xu and Clark, 1997), and protein phosphatase 2A (PP2A; Ivaska et al, 2002a). Here, PKC␣ activity was needed for the internalization of ␣2␤1 integrin in caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…The atypical PKC isoform PKC has been particularly implicated in IKK-2 activation (30) and has been shown to be inhibited by calphostin C (40). Therefore, we focussed our attention on PKC as the candidate PKC isoform mediating these effects.…”
Section: Ras and Pkc Mediate The Activation Of Nf-b By Ha Fragmentsmentioning
confidence: 99%